EDUKASI KOSMETIK AMAN DENGAN MENGGUNAKAN KOSMETIK SESUAI JENIS KULIT DAN PENCEGAHAN KRIM ILEGAL MELALUI PENGECEKAN NOTIFIKASI BPOM SECARA ONLINE DI MTsN 01 KENDARI - Astrid Indalifiany; Nur Illiyyin Akib; Afaf Nur Azizah; Desri Fitrianita; Leyin Swastini Arsyad; Nurdiana Nurdiana; Ummy Kalzum (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Cosmetic use among adolescents is increasing, but understanding of product safety and identification of illegal cosmetics remains low. This community service activity aims to provide education on safe cosmetics according to skin type and how to prevent the use of illegal creams through online BPOM notification checking. The methods used include socialization, education, and practice of checking BPOM notifications at MTsN 01 Kendari in May 2026. The outputs include increased student understanding, media publications, activity videos, and service reports. The results show that this activity effectively increases students' awareness in choosing safe cosmetics registered with BPOM.